2005
DOI: 10.1074/jbc.m508772200
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Formamidopyrimidines in DNA Involves Different Glycosylases

Abstract: The oxidatively induced DNA lesions 2,6-diamino-4-hydroxy-5-formamidopyrimidine (FapyG) and 4,6-diamino-5-formamidopyrimidine (FapyA) are formed abundantly in DNA of cultured cells or tissues exposed to ionizing radiation or to other free radical-generating systems. In vitro studies indicate that these lesions are miscoding, can block the progression of DNA polymerases, and are substrates for base excision repair. However, no study has yet addressed how these lesions are metabolized in cellular extracts. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
148
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(157 citation statements)
references
References 41 publications
(47 reference statements)
6
148
0
1
Order By: Relevance
“…One mechanism focuses on the implications for an insufficient repair of ROS-induced DNA lesions in the mitochondria. Recently, mitochondrial localization of NEIL1 was demonstrated, thus linking NEIL1 to repair of oxidative damage in mtDNA (22). Our data demonstrate significantly elevated levels of mtDNA damage and deletions, suggesting that at least a subset of lesions may not be repaired in the mtDNA genome.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…One mechanism focuses on the implications for an insufficient repair of ROS-induced DNA lesions in the mitochondria. Recently, mitochondrial localization of NEIL1 was demonstrated, thus linking NEIL1 to repair of oxidative damage in mtDNA (22). Our data demonstrate significantly elevated levels of mtDNA damage and deletions, suggesting that at least a subset of lesions may not be repaired in the mtDNA genome.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, Das et al (21) demonstrated that neil1 mRNA levels are elevated Ϸ3-fold after ROS exposure. Additionally, NEIL1 was shown to localize in both the nucleus and mitochondria (22), suggesting that this enzyme is involved in the overall maintenance of genomic stability.…”
mentioning
confidence: 99%
“…The primary substrates recognized by OGG1 include 8-oxoguanine (8-oxoG), the most commonly formed oxidative DNA lesion, and the formamidopyrimidine derivative of guanine (FapyG). Extracts from mice lacking OGG1 have consistently demonstrated increased accumulation of these lesions [Minowa et al, 2000;Nishimura, 2001;Hu et al, 2005]. However, as discussed below, the relationship between the increased number of lesions and pathological states is not always straightforward.…”
Section: Ogg1mentioning
confidence: 99%
“…A role for BER in the repair of AFB 1 -Fapy-dG in human cells has not been previously investigated. The human DNA glycosylase that is predominately responsible for the initiation of BER of Fapy adducts is hNEIL1, with substrates including the secondary oxidation products of 8-oxoG, Fapy-dA, Fapy-dG, methyl-Fapy-dG, and a subset of oxidized pyrimidines (22)(23)(24)(25)(26)(27)(28)(29)(30). In addition, this enzyme exhibits distinct structural preference for repairing lesions that are located within DNA bubble structures, modeling DNA intermediates formed during transcription and replication (29).…”
Section: Significancementioning
confidence: 99%